Forbidden - Judy Waite (Oxford Oxford University Press, 2014)
Elinor has always been one of the Chosen, from as far back as she can remember. It is her destiny to become bonded to the cult leader as soon as she turns 16, a ritual that Elinor is happy and proud to be part of. But a chance encounter in the woods stirs emotions and memories that have long been supressed. Suddenly all her beliefs are being challenged and she starts to question her role in the cult. But will she ever be able to break free of the bonds that tie her to True Cause.